2020
DOI: 10.1109/tmi.2020.2967068
|View full text |Cite
|
Sign up to set email alerts
|

Blind Source Separation for Myelin Water Fraction Mapping Using Multi-Echo Gradient Echo Imaging

Abstract: In conventional gradient-echo myelin water imaging (GRE-MWI), myelin water fraction (MWF) is estimated by fitting the multi-echo gradient recalled echo (mGRE) signal to a pre-assumed numerical model (e.g., multi-component exponential curves or three component exponential curves). However, in mGRE, imaging artifacts (e.g., voxel spread function and physiological noise) and noise render the signal to deviate from the numerical model, leading to misfit of the model parameters. Here, as an alternative to the model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
(72 reference statements)
1
6
0
Order By: Relevance
“…Interestingly, we also observe that with practical modeling errors the c3e model becomes a lot less robust than the m3e. Because their main difference is whether to model the signal phases, our result implies that the c3e is very sensitive to practical phase errors, consistent with previous studies 16,40 …”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Interestingly, we also observe that with practical modeling errors the c3e model becomes a lot less robust than the m3e. Because their main difference is whether to model the signal phases, our result implies that the c3e is very sensitive to practical phase errors, consistent with previous studies 16,40 …”
Section: Resultssupporting
confidence: 90%
“…For example, the multi‐exponential model was analyzed using numerical simulations under a wide range of noise levels and found to require very high SNR to produce reliable results 12‐14 . Similarly, 3‐exponential models were also found to be rather sensitive to noise, using simulated data with different SNRs and parameter values 15,16 . To address this issue, several methods have been developed to denoise the measured data before parameter estimation by imposing low‐rank constraints 17,18 or sparsity constraints 18 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, an extended complex GRE-MWI model with T 1 correction was used as an example of the application of vFA-EPTI for multi-compartment analysis. The proposed acquisition can also be applied to other GRE-MWI models ( Nam et al, 2015b ; Song et al, 2020 ; van Gelderen et al, 2012 ), and to single-pool quantitative mapping as we have shown in Fig. 9 and 10 .…”
Section: Discussionmentioning
confidence: 98%